A influência da LIBRAS na produção escrita do aluno surdo - (:unkn) unknown (Universidade Federal do Pampa, 2013)
This monograph presents a study about relevant aspects concerning written production of deaf students, stressing to analyze the main characteristics of a written text in Portuguese language. Aiming at comprehend LIBRAS interference – Língua Brasileira de sinais – in Portuguese language, their second language. This research was divided in two chapters focused in certain aspects and particularities of this writing, in the grammatical and structural levels of the language.
Keywords: Produção escrita; Aprendizado; LIBRAS; Written production; Learning; CNPQ::LINGUISTICA, LETRAS E ARTES